Analisis Kemampuan Berpikir Aljabar Ditinjau Dari Kepercayaan Diri Siswa - Adawiyah, Anisah Luthpi; Nur Atiqoh, Khamida Siti; Satriawati, Gusni (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
Student confidence is one of the factors that affect students' algebraic thinking skills. Algebraic thinking ability is the ability to present information mathematically through diagrams, tables, graphs, equations, and understanding of patterns, functions, structures, and uncertain objects. This study aims to describe and analyze quantitatively the algebraic thinking ability of high school students, high school students' self-confidence and know the influence between algebraic thinking ability and students' self-confidence. This research was conducted in three public high schools in South Tangerang City in the 2023/2024 school year. This research is a survey research with a correlational approach. The test instrument given was a description of algebraic thinking ability and a non-test instrument of self-confidence to 111 students. The results showed that students' algebraic thinking ability and self-confidence were in the moderate category. The results also showed that the effect between students' self-confidence on algebraic thinking ability was 33.60%. It can be concluded that if students' self-confidence is good then the ability to think algebra will also be good. The results of this study can be a consideration for teachers to develop mathematics learning activities that can increase student confidence.